Effective Droplet Size Reduction and Excellent Stability of Limonene Nanoemulsion Formed by High-Pressure Homogenizer - Hidajat, Marcel Jonathan; Jo, Wantaek; Kim, Hyeonhyo; Noh, Jongho (Colloids and interfaces, 2020)
Limonene as an interesting bioactive material that has great benefits due to its antimicrobial and anti-carcinogen properties. However, it has several limitations such as its oxidative and oily nature. In order to overcome these limitations, a high-pressure homogenizer (HPH) was utilized to produce limonene nanoemulsion, which enhances its dispersibility while preventing oxidation with great stability. Limonene was pre-mixed with soybean oil as carrier oil prior to emulsification. The effect of soybean oil to limonene ratio, number of pass, homogenization pressure, emulsifier concentration and homogenization method were observed. A stability test was also conducted for 28 days at room temperature. The result revealed that soybean oil and limonene demonstrated a certain ratio to produce the most stable nanoemulsion. Meanwhile, emulsion size could be reduced from 327.8 nm to 55.5 nm in five passes at 1000 bar. Increasing the emulsifier concentration could reduce the droplet size to 40 nm. A comparison with other emulsification method showed that HPH was the best emulsification technique due to its intense emulsification power resulted from shear, cavitation, and droplet impacts. This study reveals that HPH is a great and simple way to produce stable limonene nanoemulsion for the cosmetic, pharmaceutical, and food industries.